Transaction Cost of Forest Utilization Licenses: Institutional Issues - Hariadi Kartodihardjo; Grahat Nagara; Abdul Wahib Situmorang (Institut Pertanian Bogor (IPB University), 2015)
Forest resource management has a characteristic of high transaction cost particularly due to lack of valid information and policy process. Such characteristic requires unique institution to ensure an effective policy implementation. This study shows that state has inadequate control over forests and forest governance, extra-legal access, as well as patron-client relationships as the causes of the high transaction costs. Consequently, more and more the natural production forests are degraded and this does not only cause loss of state revenue from natural resources, but also a bankruptcy of corporations which exploit natural production forests. Most of those natural forest assets turned into resources for producing and reproducing a rival institution or extra-legal power, rendering official state institutions incapable of controlling transaction costs. Therefore, changes and improvements of the licensing arrangements need to be supported by the political elites and elite government officials in order to break the historical influence as well as to serve as a new platform for mid-level employees and government officers in implementing the national forest utilization policy.